Modeling personality structure using semantic relationships: Is the HEXACO Honesty-Humility a distinct trait? - Gill, C. M. H. D.*; Berezina, E * (Russian Psychological Society, 2019)
Background: Although the Big Five model (BFM) of personality has been the dominant paradigm in personality research since the mid-1990s, it has recently been challenged by the HEXACO model, which contains an additional factor called Honesty-Humility. Since both these models of personality were developed using the same factor analytic techniques, there has been an ongoing but inconclusive debate about the relative merits of these competing models. Objective: This paper assesses the robustness of the Honesty-Humility trait using a technique based on the semantic relationships between personality trait adjectives. Design: Trait marker adjectives for the HEXACO Honesty-Humility and BFM Agreeableness and Neuroticism personality domains in the English language are translated into, and back-translated from, six Asian languages to generate lists of closely related trait terms known as schedonyms. The numbers of schedonyms found within and across the three personality domains are then compared, to determine whether the HEXACO Honesty-Humility factor is semantically distinct from the BFM traits of Agreeableness and Neuroticism. Results: Our fndings indicate that the Honesty-Humility trait domain is semantically distinct from the BFM traits of Agreeableness and Neuroticism, and therefore that there is at least one more personality trait beyond the BFM. The implications of these fndings, and the potential applications of this semantically-based technique for establishing the universal structure of the human personality, are briefy discussed. Conclusion: Our semantic analysis provides clear evidence that there is an Honesty-Humility trait domain in addition to the Agreeableness and Neuroticism traits, and therefore that HEXACO provides a better description of human personality than the BFM.